Opportunities for Earth Observation to Inform Risk Management for Ocean Tipping Points - Richard A. Wood; Jonathan A. Baker; Grégory Beaugrand; Jacqueline Boutin; Alessandra Conversi; Reik V. Donner; Ivy Frenger; Eric Goberville; Hakase Hayashida; Wolfgang Koeve; Karin Kvale; Angela Landolfi; et al. (Surveys in Geophysics, 2025)
As climate change continues, the likelihood of passing critical thresholds or tipping points increases. Hence, there is a need to advance the science for detecting such thresholds. In this paper, we assess the needs and opportunities for Earth Observation (EO, here understood to refer to satellite observations) to inform society in responding to the risks associated with ten potential large-scale ocean tipping elements: Atlantic Meridional Overturning Circulation; Atlantic Subpolar Gyre; Beaufort Gyre; Arctic halocline; Kuroshio Large Meander; deoxygenation; phytoplankton; zooplankton; higher level ecosystems (including fisheries); and marine biodiversity. We review current scientific understanding and identify specific EO and related modelling needs for each of these tipping elements. We draw out some generic points that apply across several of the elements. These common points include the importance of maintaining long-term, consistent time series; the need to combine EO data consistently with in situ data types (including subsurface), for example through data assimilation; and the need to reduce or work with current mismatches in resolution (in both directions) between climate models and EO datasets. Our analysis shows that developing EO, modelling and prediction systems together, with understanding of the strengths and limitations of each, provides many promising paths towards monitoring and early warning systems for tipping, and towards the development of the next generation of climate models.

Inverse response of 231Pa/230Th to variations of the Atlantic meridional overturning circulation in the North Atlantic intermediate water - Finn Süfke; Hartmut Schulz; Jeemijn Scheen; Sönke Szidat; Marcel Regelous; Patrick Blaser; Frerk Pöppelmeier; Tyler J. Goepfert; Thomas F. Stocker; Jörg Lippold (Geo-Marine Letters, 2020)

Transport of salt and freshwater in the Atlantic Subpolar Gyre - Andreas Born; Thomas F. Stocker; Anne Britt Sandø (Ocean Dynamics, 2016)

Is the Atlantic subpolar gyre bistable in comprehensive coupled climate models? - Andreas Born; Thomas F. Stocker; Christoph C. Raible; Anders Levermann (Climate Dynamics, 2013)

The freshwater balance of polar regions in transient simulations from 1500 to 2100 AD using a comprehensive coupled climate model - Flavio Lehner; Christoph C. Raible; Dominik Hofer; Thomas F. Stocker (Climate Dynamics, 2012)

The IPCC AR5 guidance note on consistent treatment of uncertainties: a common approach across the working groups - Michael D. Mastrandrea; Katharine J. Mach; Gian-Kasper Plattner; Ottmar Edenhofer; Thomas F. Stocker; Christopher B. Field; Kristie L. Ebi; Patrick R. Matschoss (Climatic Change, 2011)

Uncertainty and risk in climate projections for the 21st century: comparing mitigation to non-intervention scenarios - Lorenzo Tomassini; Reto Knutti; Gian-Kasper Plattner; Detlef P. van Vuuren; Thomas F. Stocker; Richard B. Howarth; Mark E. Borsuk (Climatic Change, 2010)

Simulated decadal oscillations of the Atlantic meridional overturning circulation in a cold climate state - Masakazu Yoshimori; Christoph C. Raible; Thomas F. Stocker; Manuel Renold (Climate Dynamics, 2010)

A European pattern climatology 1766–2000 - Carlo Casty; Christoph C. Raible; Thomas F. Stocker; Heinz Wanner; Jürg Luterbacher (Climate Dynamics, 2007)

Challenges posed by and approaches to the study of seasonal-to-decadal climate variability - Cornelia Schwierz; Christof Appenzeller; Huw C. Davies; Mark A. Liniger; Wolfgang Müller; Thomas F. Stocker; Masakazu Yoshimori (Climatic Change, 2006)

The coupling of optimal economic growth and climate dynamics - Olivier Bahn; Laurent Drouet; Neil R. Edwards; Alain Haurie; Reto Knutti; Socrates Kypreos; Thomas F. Stocker; Jean-Philippe Vial (Climatic Change, 2006)

On the interpretation of low-latitude hydrological proxy records based on Maunder Minimum AOGCM simulations - Masakazu Yoshimori; Christoph C. Raible; Thomas F. Stocker; Manuel Renold (Climate Dynamics, 2006)